2013
DOI: 10.3168/jds.2012-6124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PCR electrospray-ionization mass spectrometry for rapid molecular diagnosis of bovine mastitis

Abstract: Bovine mastitis, an inflammatory disease of the mammary gland, is one of the most costly diseases affecting the dairy industry. The treatment and prevention of this disease is linked heavily to the use of antibiotics in agriculture and early detection of the primary pathogen is essential to control the disease. Milk samples (n = 67) from cows suffering from mastitis were analyzed for the presence of pathogens using PCR electrosprayionization mass spectrometry (PCR/ESI-MS) and were compared with standard cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…In six cases, the authors were unable to identify species of CNS causing subclinical mastistis using MALDI-TOF MS (log value less than 2.0). Similar results were obtained by Perreten et al (2013), who were unable to determine the primary etiological factor of mastitis in 18% of disease cases using the PCR/ESI-MS technique. Other studies (Tomazi et al 2014) demonstrated that the sensitivity of MALDI-TOF MS for the identification of CNS isolated from cow udders is 95.4% in comparison to PCR-RFLP.…”
Section: Discussionsupporting
confidence: 83%
“…In six cases, the authors were unable to identify species of CNS causing subclinical mastistis using MALDI-TOF MS (log value less than 2.0). Similar results were obtained by Perreten et al (2013), who were unable to determine the primary etiological factor of mastitis in 18% of disease cases using the PCR/ESI-MS technique. Other studies (Tomazi et al 2014) demonstrated that the sensitivity of MALDI-TOF MS for the identification of CNS isolated from cow udders is 95.4% in comparison to PCR-RFLP.…”
Section: Discussionsupporting
confidence: 83%
“…In the same way, it is also possible to design a more complex form in which variable number of forward primers is added to face less number of reverse primers in the reaction. This reduction in the number of primers in the reactions minimizes possible faulty annealing or dimer building [3] . Another variant is the combination of different assays together such as performing Multiple PCR followed by electrospray-ionization mass spectrometry (PCR/ESI-MS) in order to enable rapid detection of nearly all known pathogens.…”
Section: Other Variants Of Pcrmentioning
confidence: 99%
“…Mastitis pathogens are usually bacteria, however, molds, yeast, and prototheca may also induce mastitis. It is important to identify the mastitis prompting organism in order to (1) properly treat and select the suitable antibiotics, (2) understand their route of spread and evaluate the contagiousness of the case, (3) calculate their public health impact, (4) to judge the prognosis of the affected quarter/cow considering early culling decision, (5) select the suitable hygienic and preventive measures, and finally for (6) choosing the proper mastitis vaccine programs to be applied in the farm [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With broad-range amplification followed by detection of mixed amplicons, the process can identify genetic proof of known and unknown pathogens. Perreten and colleagues demonstrated that PCR-ESI-MS, a more rapid diagnostic platform compared with bacterial culture, has the significant potential to serve as an important screening method in the diagnosis of bovine clinical mastitis and has the capacity to be used in infection control programs for both subclinical and clinical disease [78]. Identification by PCR-ESI-MS using oligonucleotides is more specific for bacterial groups than for particular species, even if changeable regions are amplified between species and strains.…”
Section: Pcr Coupled To Mass Spectrometry Using Electrospray Ionizatimentioning
confidence: 99%